Kinematics Analysis and Simulation of a 4-CPS/UPU Parallel Mechanism - Liu Juan; Li Ruiqin; Wang Yuan; Ning Fengping (Jixie chuandong)
A 4-CPS/UPU parallel mechanism used in the field of parallel machine tools is proposed. Based on the screw theory, the kinematic and constrained screw system of the parallel mechanism is established. The mechanism has five degrees of freedom and can realize the function of three shifts and two rotations. The degree of freedom is verified by the modified K-G formula. The forward and inverse solutions of the parallel mechanism and the working space are analyzed. The simulation analysis is carried out by Adams software. The workspace of the mechanism is continuous without cavity, and its shape is similar to that of a pyramid, which is regular and symmetrical; the smooth displacement and velocity curves obtained by simulation show that the mechanism has good kinematic performance, which provides a certain theoretical basis for its parametric design in the field of parallel machine tools.